2015
DOI: 10.1007/s10563-015-9195-1
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks for Catalysis

Abstract: Metal-organic frameworks (MOFs) are a relatively new class of porous material, which are comprised of metal ions or clusters linked with poly-functional organic molecules. MOFs have been studied increasingly for heterogeneous catalysis applications because these hybrid materials have well-ordered tunable porous structures with exceptional textural properties and introduction of additional active sites can be carried out easily by relatively simple post-synthesis functionalization. This short review focuses on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 93 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…18,[22][23][24][25][30][31][32][33][34][35][36][37][38][39][40][41][42][43] In recent years, porous IMAC materials also have been widely applied in phosphopeptides researches due to its merits of large surface area, unique pore volume, and regular porous structure. 37,40,[44][45][46] Metal-organic frameworks (MOFs), as a type of ordered porous IMAC materials, have been applied in storage, 47 separation, [48][49][50][51] sensing, 52 drug delivery 53 and catalysis 54,55 because of their super high porosity, well-dened porous structure and super large surface areas. Recently, it has been reported that MOFs could function as sorbents for the separation and enrichment of phosphopeptides owing to the presence of plenty of Lewis acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…18,[22][23][24][25][30][31][32][33][34][35][36][37][38][39][40][41][42][43] In recent years, porous IMAC materials also have been widely applied in phosphopeptides researches due to its merits of large surface area, unique pore volume, and regular porous structure. 37,40,[44][45][46] Metal-organic frameworks (MOFs), as a type of ordered porous IMAC materials, have been applied in storage, 47 separation, [48][49][50][51] sensing, 52 drug delivery 53 and catalysis 54,55 because of their super high porosity, well-dened porous structure and super large surface areas. Recently, it has been reported that MOFs could function as sorbents for the separation and enrichment of phosphopeptides owing to the presence of plenty of Lewis acid sites.…”
Section: Introductionmentioning
confidence: 99%
“…MOFs are also called coordination polymers composed of organic and inorganic segments wherein the linkage between two metals are bivalent or trivalent aromatic carboxylic acids or nitrogen containing aromatics (Bhattacharjee, Lee, Puthiaraj, Cho, & Ahn, 2015;Lee, Kim, & Ahn, 2013;Sun, Qin, Wang, & Su, 2013). The outstanding features of these hybrid structures such as high specific surface are, very little blocked pores, narrow pore size distribution have made these hybrid structures better than traditional mesoporous structures (Keskin & Kızılel, 2011) and ideal candidates for various applications (Gao, Hai, Baigude, Guan, & Liu, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are new nanoporous frameworks with periodic network structure formed by self-assembling of nitrogen or oxygen-containing organic ligands and transition metal ions through complexation [16]. MOFs have well-ordered tunable porous structures with a wide range of pore sizes and exceptional textural properties of high surface areas and high pore volumes, which can afford a variety of applications in gas adsorption/separation and heterogeneous catalysis [17]. When MOFs is used as a homogeneous catalyst, it has been used for the following reactions: (a) aerobic oxidation of tetralin [18,19], (b) phenol hydroxylation [20], (c) oxidative desulfurization of dibenzothiophene [21], (d) Knoevenagel condensation reaction [22,23], (e) one pot deacetalization-nitroaldol reaction [24], (f ) Friedel-Craft acylation [25], (g) CO 2 cycloaddition of epoxides [26], (h) heck reaction [27], and (i) epoxidation of alkenes [28].…”
Section: Introductionmentioning
confidence: 99%